Characterization of Site Amplification by a Parametric Study - FERCAN, NAZİFE ÖZGE; Şafak, Erdal; Ansal, Atilla (Taylor & Francis Inc., 2023)
The reliability of Vs30 and the performance of alternative time averaged shear wave velocities (Vsz) and shear wave travel times (Ttz) at various depths, z, were investigated for the estimation of site amplification and fundamental frequency (f0) characterization by considering the linear and nonlinear soil behavior. The study revealed that alternative parameters performed better than Vs30 and the best performing z parameters changed by switching from convex to concave theoretical profiles and by increasing ground motions. For a practical usage in site investigations, guidelines to estimate nonlinear soil amplification factor and fundamental frequency from the linear ones were presented.
Keywords: Site Amplification; Fundamental Soil Frequency; Nonlinear Soil Behavior; Time Averaged Shear Wave Velocity; Shear Wave Travel Time; Impedance Ratio